187k views
0 votes
The sum of 6c - 5 and the opposite of 6c
(6c - 5) + (-6c)

User Gusgard
by
5.2k points

2 Answers

6 votes

The sum 6c−5 and the opposite of 6c is −5.

To find the sum, you can combine like terms:

(6c - 5) + (-6c)

Combine the "6c" and "-6c" terms:

= 6c - 6c - 5

Now, combine the "6c" and "-6c" terms, which result in 0:

= -5

So, the sum 6c−5 and the opposite of 6c is −5.

Question

Problem set Fill in the missing parts. a. The sum of 6c-5 and the opposite of 6c (6c-5)+(-6c) Rewrite subtraction as addition 6c+(-6c)+(-5) 0+(-5) Additive identity property of zero.

User Dewald
by
5.3k points
4 votes

Answer:

There are no real solutions for the given question (6c - 5) + (-6c)

Explanation:

Solution for (6c-5) + (-6c)

Simplifying ,

(6c + -5) + (-6c) = 0

Reordering the given terms:

(-5 + 6c) + (-6c) = 0

Remove "parenthesis" around (-5 + 6c)

-5 + 6c + (-6c) = 0

Combining like terms it becomes 6c + (-6c) = 0

-5 + 0 = 0

-5 = 0

Solving

-5 = 0

we could not find the solution for the given (6c - 5) + (-6c).

The given equation is not a valid one, the "left hand side" and "right hand side" are unequal, and therefore there is no solution.

User Rdh
by
5.5k points